(untitled) (Social and Environmental Law Journal, 2024)
The environment is a combination of biological, physical and chemical elements that create the conditions for life on the planet, including human beings with their social, cultural and economic dynamics. Within this perspective, the persent work focuses on the relationship between Man and the Environment and its Social Representation, with the support of the 1988 Federal Constitution, which recognizes the environment as a common and essential good for quality of life. The misuse of natural resources has become increasingly common. In this context the objective of this work is to raise and analyze issues through research and the Social Representation of Students, Teachers and Society in general regarding the environment in which they live. The goal is to obtain answers about their concerns, proposing a reflection on the thoughts, behavior and actions of individuals. The theory of Social Representations, conceived in France in the 1960s by Serge Moscovici, is used for this purpose. It is a socio-psychological theory that can be defined as a form of knowledge transmitted by society and shared by a social group. To clarify all this, this work uses research, graphs and statistics that depict a frightening picture. If Brazil and other countries do not take a firm stance in defense of the environment, as proposed by organizations such as the UN, there will be no prosperity for species.